Alternative Dispute Resolution In Medical Dispute Resolution: Initiating The Establishment Of An Alternative Medical Dispute Resolution Institution In Indonesia - Istiana Sari; Yasarman (SEAN Institute, 2025)
Medical disputes are disputes that occur between a patient or a patient's family and a doctor/health worker or between a patient and a health facility regarding matters related to patient services, treatment and care. Resolving medical disputes through the courts takes a long time, the cost of cases is expensive, decisions do not always solve problems, cause estrangement between the parties, judges' decisions are unpredictable, judges do not understand the ins and outs of medicine. In some countries, 67.8% of medical disputes can be resolved through mediation. For this, Alternative Dispute Resolution or alternative dispute resolution outside the judicial system is needed.Alternative Dispute Resolution can be done by negotiation, mediation, conciliation and arbitration. Medical dispute resolution with alternative dispute resolution in Indonesia has not been comprehensively regulated. There is no state institution that handles alternative medical dispute resolution in Indonesia. In this study, the researcher used a normative juridical research method. Normative qualitative research specifications with empirical, analytical descriptive, and analytical prescriptive. The conclusion reached is that medical problems are special and can be resolved by alternative dispute resolution. For this reason, an Alternative Medical Dispute Resolution Institution in Indonesia is needed.